Characteristics of medial-lateral postural control while exposed to the external perturbation in step initiation - Lee, Yun-Ju (Sci Rep, 2019)
Controllability of posture in the medial-lateral direction is critical for balance maintenance, particularly in step initiation. The objective of the current study was to examine  the effects of external perturbation and landing orientation on medial-lateral control stability in step initiation. Eleven young healthy participants stood on the force platform and waited for the instruction of taking a step while experiencing a pendulum perturbation applied at the lateral side of the right shoulder. Eight experimental conditions were conducted by two levels of step side (right or left), two levels of perturbation (with or without), and two levels of landing orientation (forward or diagonal). The center of pressure (COP), pelvic movements, and muscle activities were recorded and analyzed as the onset of COP and pelvic movement, the COP displacement, and cocontraction and reciprocal muscle activation pattern. The temporal events of COP and pelvic movement were not significantly different in all experimental conditions. However, COP and pelvic movement were significantly later in the diagonal condition. Most of the segments showed reciprocal muscle activation patterns in relation to the perturbation released time. Subsequently, all segments showed cocontraction muscle activation patterns, which was significantly affected by step side, perturbation, and orientation. The results suggest that how the CNS initiated a step was identical with the COP then pelvic movement. The outcome highlights the importance of external perturbation and foot landing orientation effects on postural adjustments, which may provide a different approach to help step initiation.